2006
DOI: 10.1099/vir.0.81453-0
|View full text |Cite
|
Sign up to set email alerts
|

A new promoter-binding site in the PB1 subunit of the influenza A virus polymerase

Abstract: The influenza A virus RNA-dependent RNA polymerase consists of three subunits PB1, PB2 and PA. The 59 and 39 terminal sequences of the viral RNA (vRNA) form the viral promoter and are bound by the PB1 subunit. The putative promoter-binding sites of the PB1 subunit have been mapped in previous studies but with contradictory results. The aim of the current study was to investigate the function of two evolutionary conserved regions in PB1 -from aa 233 to 249 and 269 to 281, which lie immediately N-and C-terminal,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
27
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 29 publications
4
27
0
Order By: Relevance
“…As both subunits have been implicated in promoter binding 24 , we speculate that association with NEP might also lead to a stabilization of cRNPs, thereby increasing the synthesis of vRNA transcripts, as suggested by others 25 .…”
Section: Discussionsupporting
confidence: 61%
“…As both subunits have been implicated in promoter binding 24 , we speculate that association with NEP might also lead to a stabilization of cRNPs, thereby increasing the synthesis of vRNA transcripts, as suggested by others 25 .…”
Section: Discussionsupporting
confidence: 61%
“…1a), using them to co-purify RanBP5 from 293T cells. PB1 was divided into an N-terminal fragment containing the PA-binding and promoter-binding domains (residues 1-290), a middle fragment containing the core RdRP motifs (residues 289-488) and a C-terminal fragment containing the PB2-binding site (residues 488-757) (Jung & Brownlee, 2006;Sugiyama et al, 2009;Ruigrok et al, 2010). Efficient binding of RanBP5 was observed with full-length tagged PB1 and with the N-terminal fragment of PB1, but not with the middle or C-terminal fragments of the protein (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…4a). Nor do the mutations overlap known promoter-binding or polymerase motifs (González & Ortín, 1999;Jung & Brownlee, 2006;Li et al, 1998; Müller et al, 1994;Poch et al, 1989). A previous study has shown that the NLS2 mutation did not substantially affect the ability of PB1 to transcribe and replicate a template RNA [a negative-sense chloramphenicol acetyltransferase (CAT) gene flanked by the untranslated regions of WSN segment 8] in an RNP reconstitution (Fodor & Smith, 2004); we confirmed this observation using full-length vRNA and cRNA of WSN segment 6 as a template (data not shown).…”
Section: E C Hutchinson and Others 1862mentioning
confidence: 99%
“…The PB1 subunit of the viral RdRP can be phosphorylated at position T223. This is close to a nuclear localization signal (NLS) and a region that is believed to be involved in promoter binding, indicating a potential role in regulating the cellular localization or RNA binding of PB1 (36,90,(117)(118)(119)(120).…”
Section: Discussionmentioning
confidence: 99%